Long-Term Variability of the Kuroshio Shelf Intrusion and Its Relationship to Upper-Ocean Current and Temperature Variability in the East China Sea - Kang, Jiwon; Na, Hanna (Frontiers in Marine Science, 2022)
The strong variability of the Kuroshio northeast of Taiwan is associated with changes in the strength of the Kuroshio shelf intrusion (KSI) in the East China Sea (ECS), which is a westward shift in the Kuroshio toward the shelf region. The KSI contributes to the exchange of different water masses between the shelf and the western boundary current regions, and plays a key role in ecosystem and climate regulation in the ECS and the downstream East Asian Marginal Seas. This study investigates the long-term variability of the KSI northeast of Taiwan during 1993–2018 and examines its relationship to the current and temperature variability in the ECS using a high-resolution ocean reanalysis dataset. The KSI was notably strengthened in 2000–2001, 2005, and 2009. It showed stronger interannual variability during the 2000s, whereas it was relatively stable in the 1990s and the 2010s. The strengthening of the KSI is accompanied by a westward shift of the Kuroshio axis, extending along its downstream path in the ECS. The associated warming is significant at depths >∼50 m but not near the surface. The resultant weakening of the vertical stratification in the shelf region would have important implications for ecosystem variability in the ECS.